2015
DOI: 10.3892/etm.2015.2532
|View full text |Cite
|
Sign up to set email alerts
|

Biological effects of pyrroloquinoline quinone on liver damage in Bmi-1 knockout mice

Abstract: Abstract. Pyrroloquinoline quinone (PQQ) has been demonstrated to function as an antioxidant by scavenging free radicals and subsequently protecting the mitochondria from oxidative stress-induced damage. The aim of the present study was to investigate whether PQQ is able to rescue premature senescence in the liver, induced by the deletion of B cell-specific Moloney MLV insertion site-1 (Bmi-1), by inhibiting oxidative stress. In vivo, the mice were allocated into three groups that underwent the following treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Recently, PQQ has received increasing attention due to its role in free radical scavenging. Previous studies have shown that PQQ played a significantly protective role in the parotid gland, liver, kidney, and bone by inhibiting the oxidative stress and DNA damage from exposure to deleterious events 25-29. Recent study has demonstrated that PQQ has an inhibitory effect on osteoclast differentiation in vitro 30.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, PQQ has received increasing attention due to its role in free radical scavenging. Previous studies have shown that PQQ played a significantly protective role in the parotid gland, liver, kidney, and bone by inhibiting the oxidative stress and DNA damage from exposure to deleterious events 25-29. Recent study has demonstrated that PQQ has an inhibitory effect on osteoclast differentiation in vitro 30.…”
Section: Introductionmentioning
confidence: 99%
“…B lymphoma Mo-MLV insertion region 1 (BMI1), a member of the polycomb transcriptional repressors proteins, was first identified as a proto-oncogene and has since been associated with cell cycle, stem cell maintenance and oncogenesis [17][18][19]. Mice without BMI1 display premature aging of the entire body, including brain, hematopoiesis, bone, kidney, liver and ovary [20][21][22][23][24][25], suggesting that this protein exerts antiaging effects. Mechanistically, BMI1 can transcriptionally repress the expressions of cell cycle dependent kinase inhibitors, p16 and p19, which regulate cell cycle, senescence, and apoptosis [26].…”
Section: Introductionmentioning
confidence: 99%
“…The substance that is postulated to possess the ability to promote the mitochondrial biogenesis is pyrroloquinoline quinone (PQQ) [107, 108]. This substance is also postulated to be OS protective [109]. …”
Section: Therapeutic Conclusionmentioning
confidence: 99%